Reading Assessment for Diagnosing Acquired Reading Disorders in Adults: Theoretical and Practical Aspects of its Development - Kis, Orsolya; Földi, Fanni; Steklács, János (Central European Journal of Educational Research, 2023)
The study of reading processes is of particular importance in the assessment of cognitive-linguistic functions in both atypical development and acquired disorders of the adult developmental skills system. A comprehensive assessment of cognitive processes allows the selection of the appropriate therapeutic techniques, which in turn contributes to the best possible quality of life following rehabilitation. A common leading symptom of cognitive dysfunction in adult acquired neurological impairment is a deficit in reading. Our aim was to develop a reading assessment procedure based on national and international theoretical and empirical research to allow a complex assessment of reading processes. In order to investigate the reliability of the test and to develop an assessment system for it, a large-scale survey was organised. During the analyses, an evaluation system was developed which would allow us to objectively describe not only the fact of impairment but also its extent. Based on our results, the design of the Adult Acquired Reading Assessment and the comprehensive assessment system associated to it have resulted in a complex test procedure that is not only well applicable in clinical diagnostics but also in exploratory empirical work.